Pengaruh Self-Congruity Terhadap Brand Loyalty Pada Pengguna Telepon Genggam Nokia - Elny Widjaja; Anton Wachidin Widjaja (Ultima Management : Jurnal Ilmu Manajemen, 2009)
Nowadays, the development of telecommunication industry has showed rapid progress. It is indicated by numerous new comer of cellular phone companies enter the industry with different competitive technology in order to attract customer interest. Such tight competition results in increasing loyalty in certain brand. Until today, no research has put their observation into the influence of self-congruity to brand loyalty, although consumer goods industry is an important and significant sector in Indonesia. The research analyzes positive influence both directly and indirectly to self congruity through functional congruity, product involvement, and brand relationship of Nokia cell phone consumer. Selfcongruity can give direct influence to brand loyalty and it can also give indirect influence to brand loyalty through product involvement, Brand relationship quality, and functional congruity. 200 respondents have participated in the research. Structural Equation Marketing is used to test eight hypotheses which state the influence among variables in the research model. Result indicates that self-congruity has influenced brand loyalty for Nokia cell phone consumer, whether functional congruity has not influenced brand loyalty of Nokia cell phone consumer. Keywords: Telecommunication, brand loyalty, self congruity, functional congruity, Nokia,product involvement